The effects of music listening interventions on cognition and mood post-stroke: a systematic review. (1st November 2016) - Baylan, Satu; Swann-Price, Rhiannon; Peryer, Guy; Quinn, Terry
ABSTRACT: Introduction : Music listening may have beneficial psychological effects but there has been no comprehensive synthesis of the available data describing efficacy of music listening in stroke. Areas covered : We performed a systematic review examining the effects of music listening interventions on cognition and mood post-stroke. We found five published trials (n = 169 participants) and four ongoing trials. All studies demonstrated benefits of music listening on at least one measure of cognition or mood. Heterogeneity precluded meta-analysis and all included studies had potential risk of bias. Common reporting or methodological issues including lack of blinding, lack of detail on the intervention and safety reporting. Expert commentary : It is too early to recommend music listening as routine treatment post-stroke, available studies have been under-powered and at risk of bias. Accepting these caveats, music listening may have beneficial effects on both mood and cognition and we await the results of ongoing controlled studies.